The Relationship Between Economic Value Added, Market Value Added And Return On Cost Of Capital In Measuring Corporate Performance - Suwinto Johan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of the paper is to assess the relationship between Economic Value Added (EVA), Market Value Added (MVA) and the traditional financial ratio in measuring investment performance by a holding company. The sample is PT. Astra International, Tbk in Indonesia. Astra is one of the largest conglomerate in Indonesia with diversify business from automotive, financial service, agro, infrastructure and technology. All of the investments are consolidated under single company, which is PT. Astra International, Tbk. The research assessed the financial performance from 2009 – 2016. The research will use Economic Value Added (EVA), Market Value Added (MVA) and Return on Weighted Average Cost of Capital (ROC) as financial measurement tools. The research found that there was a direct relationship between ROC and EVA. Negative EVA and negative ROC did not reflect the MVA on company performance. Negative EVA and ROC, could have positive Market Value Added (MVA). However negative MVA value will also reflect on negative EVA and ROC.